Inhibition of Protein Kinase Cβ Does Not Improve Endothelial Function in Type 2 Diabetes - Beckman, Joshua A.; Goldfine, Allison B.; Goldin, Alison; Prsic, Adnan; Kim, Sora; Creager, Mark A. (The journal of clinical endocrinology and metabolism, 2010)
Context: Antagonism of protein kinase Cβ (PKCβ) restores endothelial function in experimental models of diabetes and prevents vascular dysfunction in response to hyperglycemia in healthy humans. Objective: We tested the hypothesis that PKCβ antagonism would improve vascular function in subjects with type 2 diabetes compared with healthy control subjects. Design: The effect of PKCβ was evaluated in a randomized, placebo-controlled, double-blinded crossover trial. Setting: The study was performed in the outpatient setting of a university medical center. Participants: Thirteen subjects with type 2 diabetes without evidence of cardiovascular disease and 15 healthy control subjects were recruited via newspaper advertisement. Intervention: Subjects underwent a randomized, double-blind, crossover, placebo-controlled trial of the selective PKCβ antagonist ruboxistaurin mesylate. Subjects received each treatment for 14 d. Main Outcome Measure: Endothelium-dependent and endothelium-independent vasodilation of forearm resistance vessels was measured with mercury-in-silastic, strain-gauge plethysmography during intraarterial administration of methacholine chloride and verapamil, respectively. Markers of inflammation, fibrinolysis, endothelial damage, and oxidative stress were measured after each treatment. Results: Endothelium-dependent vasodilation of forearm resistance vessels was attenuated in diabetic subjects when compared with healthy subjects (P = 0.001). Endothelium-independent vasodilation did not differ between groups (P value not significant). Ruboxistaurin did not significantly change endothelium-dependent or endothelium-independent vasodilation or blood-based markers of inflammation, fibrinolysis, endothelial damage, and oxidative stress in either diabetic or healthy subjects. Conclusion: Endothelial dysfunction of forearm resistance vessels was not improved by 2 wk of selective PKCβ inhibition in patients with diabetes. These results suggest that PKCβ does not contribute significantly to vascular dysfunction in otherwise healthy patients with type 2 diabetes.